2020
DOI: 10.1155/2020/6152612
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Occupational Injury among Hydropower Dam Construction Workers, South East Ethiopia, 2018

Abstract: Background. Occupational injuries pose a major public health and socioeconomic developmental problems. Globally, 160 million people encounter occupational injuries; the International Labour Organization estimates that the cost is 4% of the global gross domestic product (GDP) or 1.25 trillion United States Dollar (USD). The second-largest number of occupational injuries was reported from the construction industries. There are limited studies about the prevalence and factors associated with occupational injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…The possibility is the variation in types of manufacturing industries involved in this study compared to a single type of manufacturing industry in the previous study. The study showed a significant association between working hours in a week and occupational injury (χ 2 = 7.331, p = 0.007), similar findings were demonstrated [ 8 ]. Workers who worked more than 48 h are 2.3 times more likely to have an occupational injury than those who worked equal or fewer than 48 h.…”
Section: Discussionsupporting
confidence: 79%
“…The possibility is the variation in types of manufacturing industries involved in this study compared to a single type of manufacturing industry in the previous study. The study showed a significant association between working hours in a week and occupational injury (χ 2 = 7.331, p = 0.007), similar findings were demonstrated [ 8 ]. Workers who worked more than 48 h are 2.3 times more likely to have an occupational injury than those who worked equal or fewer than 48 h.…”
Section: Discussionsupporting
confidence: 79%
“…The multivariable logistic regression analysis included all variables, both statistically significant (p ≤ 0.05) and non-significant variables in the univariate regression. The non-significant variables including age, work experience, cadre of work, work hours per week, provision of PPE and level of education were included in the model because they have been reported in the literature to have a significant effect on the occurrence of occupational injuries [ 17 , 18 , 34 , 35 ]. A backward stepwise regression analysis (at p = 0.05) was used to control the non-significant variables that were deemed important.…”
Section: Methodsmentioning
confidence: 99%
“…When the "type of injury" variable was examined, it is found that "drowning" and "falling from height" were the prime causes of accidents with data showing 34.1% and 14.8% frequencies, respectively. According to Hussen et al (2020) falling from height is the most common type of injury in dam construction [25]. It is also observed from the studies that asphyxia (29.5%) and fractures (13.6%) were the most encountered injuries.…”
Section: Causes Of Accidents In Operation and Maintenance Of Dams Res...mentioning
confidence: 95%
“…Based on the various studies [21][22][23][24], it is concluded that rate of severe accidents and fatal accidents that occur in dam construction very high and alarming when compared to other construction sites. Hussen et al (2020) revealed that the annual occupational injury prevalence of the dam construction site was 57.8% [25]. Further, Yılmaz and Başağa (2018) also stated that dam constructions are the second most hazardous construction site where accidents occur at a rate of 19.6% [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation